2016
DOI: 10.1002/anie.201606544
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Aggregation‐Induced Backbone Conformational Changes in Tau Peptides

Abstract: In tau proteins, the hexapeptides in the R2 and R3 repeats are known to initiate tau fibril formation, which causes a class of neurodegenerative diseases called the taupathies. We show that in R3, in addition to the presence of the hexapeptides, the correct turn conformation upstream to it is also essential for producing prion-like fibrils that are capable of propagation. A time-dependent NMR aggregation assay of a slow fibril forming R3-S316P peptide revealed a trans to cis equilibrium shift in the peptide-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The 20 amino acid peptide, chosen in the current investigation (Tau 305–324 ), contains the short amino acid sequence 306 VQIVYK 311 which plays a crucial role in its nucleation and self-assembly, leading to β-sheet formation. Recent investigations using the above sequence have shown that the Tau peptide undergoes conformational changes in the presence of heparin, leading to the initiation of aggregation. , However, the conventional methods for detecting aggregation (for, e.g., CD, Thio T assay) require higher concentrations of peptide. On addition of heparin to the Rh-PP-InP construct, an inhibition of energy transfer occurs, which is probed using emission spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The 20 amino acid peptide, chosen in the current investigation (Tau 305–324 ), contains the short amino acid sequence 306 VQIVYK 311 which plays a crucial role in its nucleation and self-assembly, leading to β-sheet formation. Recent investigations using the above sequence have shown that the Tau peptide undergoes conformational changes in the presence of heparin, leading to the initiation of aggregation. , However, the conventional methods for detecting aggregation (for, e.g., CD, Thio T assay) require higher concentrations of peptide. On addition of heparin to the Rh-PP-InP construct, an inhibition of energy transfer occurs, which is probed using emission spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Because these findings suggested that Pc values may significantly affect cross-seeding efficiency, we reviewed a series of cross-seeding experiments of an amyloidogenic peptide derived from tau protein (R3) and its variants, e.g. C-terminally-truncated variants and substitution variants with the serine at residue 316 replaced by either proline (R3-S316P) or alanine (R3-S316A) [ 16 ]. Experiments showed that fibril formation by R3-316P alone was very slow but could be enhanced by adding fibrils of wild-type R3 or other variants as a seed.…”
Section: Resultsmentioning
confidence: 99%
“…C . Pβ graphs of tau-derived amyloidogenic peptide, R3, and its substitution variants, R3-S316A and R3-S316P, whose serine residue at the codon 316 was replaced with alanine or proline, respectively [ 16 ]. The two variants had Pβ peaks at different positions (red and blue arrows).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these data demonstrate the major effect of P32 conformation on β2m aggregation ( Torbeev and Hilvert, 2013 ). To study the role in the aggregation process of a kink within the R3 repeat of the tau protein, at residue S316, a peptide was used containing a S316P mutation ( Jiji et al, 2016 ). In the peptide wherein (2S,4S)-fluoroproline at position 316 was introduced, the cis conformation is favored compared to regular prolines and the modified peptide aggregates twice as fast.…”
Section: Detecting and Characterizing Amyloids With Chemical Biology ...mentioning
confidence: 99%